1847 Conn. Acts 11 - (:unkn) unknown (My University, 1847)
An Act Relating To Cemeteries, chap. 9: Prohibited the discharge of any gun or other firearm within any cemetery. Violators fined not exceeding one hundred dollars, or by imprisonment not exceeding six months, or both at the discretion of the court.
Keywords: DISCHARGE